2005
DOI: 10.1200/jco.2005.14.779
|View full text |Cite
|
Sign up to set email alerts
|

Late Side Effects of Short-Course Preoperative Radiotherapy Combined With Total Mesorectal Excision for Rectal Cancer: Increased Bowel Dysfunction in Irradiated Patients—A Dutch Colorectal Cancer Group Study

Abstract: Although preoperative short-term radiotherapy for rectal cancer results in increased local control, there is more long-term bowel dysfunction in irradiated patients than in patients who undergo TME alone. Rectal cancer patients should be informed on late morbidity of both radiotherapy and TME. Future strategies should be aimed at selecting patients for radiotherapy who are at high risk for local failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
503
2
23

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 837 publications
(550 citation statements)
references
References 25 publications
22
503
2
23
Order By: Relevance
“…Although radiotherapy has been shown to improve outcome for patients with resectable rectal cancer, subgroup analysis from the Dutch trial showed that there is no benefit for patients with UICC tumour stage I or IV in the upper part of the rectum [6]. Therefore it is important to improve selection criteria for the application of preoperative radiotherapy to protect patients from the side effects of radiation without benefit [27,28]. In our analysis we could show that optimal TME quality is feasible in all stages of rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although radiotherapy has been shown to improve outcome for patients with resectable rectal cancer, subgroup analysis from the Dutch trial showed that there is no benefit for patients with UICC tumour stage I or IV in the upper part of the rectum [6]. Therefore it is important to improve selection criteria for the application of preoperative radiotherapy to protect patients from the side effects of radiation without benefit [27,28]. In our analysis we could show that optimal TME quality is feasible in all stages of rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The TTM presented sequentially a short description of the two treatments and the respective probabilities of side effects as had been established at 2-year (sexual dysfunction; Marijnen et al, 2005) and 5-year (incontinence; Peeters et al, 2005) follow-up. Figure 1 depicts the male version.…”
Section: Methodsmentioning
confidence: 99%
“…Five-year follow-up trial data confirmed a reduced recurrence rate (from 11 to 6%), still with no survival benefit (Peeters et al, 2006). Irradiated patients reported higher rates of faecal incontinence compared to non-irradiated patients at 2-and 5-year follow-up Peeters et al, 2005). The Swedish Rectal Cancer Trial showed comparable results at a mean of 6 years follow-up (Dahlberg et al, 1998).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Bladder problems were observed in 2% [36]. In the TME trial, bowel dysfunction impairing daily life occurred in 34%, daily incontinence in 14% [30]. Radiation toxicity has been substantially reduced since data of large studies analyzing the pattern of local failure permitted a reduction of field size [26].…”
Section: Should the Level Of Evidence Be Neglected?mentioning
confidence: 99%